Congruent assessment of human hypoglycemic effect through STZ-induced diabetic rats fed Dromedary Camel (Camelus dromedarius) milk: DOI: 10.48129/kjs.16777 - AL-Saffar, Amal M.; a. Baker, Sirar; A. Al-Sughayer , Mona (Kuwait Journal of Science, 2022)
Diabetes mellitus (DM), a heterogeneous metabolic disorder, affect people at any point of their lives. Globally, a wide variation in the prevalence of diabetes was observed but, showed zero percent within people that regularly consume camel milk because of their highly nutritional and therapeutic potentials to treat many metabolic and autoimmune diseases. The present study validated the efficacy of camel milk by investigating the differential hypoglycemic effects in concurrence with related biochemical tests in rats fed with raw and pasteurized milk of the onehumped Arabian camel (Camelus dromedarius). Male Sprague-Dawley rats (60mg.Kg-1 body weight) fed separately with raw and pasteurized camel milk for three weeks and injected with streptozotocin induced DM besides the investigation on the levels of blood glucose, cholesterol, triacylglycerol (TAG), and insulin. Results showed a significant hypoglycemic effect with both raw and pasteurized camel milk but, more prominent with the raw milk. Three weeks consumption of raw camel milk significantly increased blood cholesterol levels while consumption of pasteurized camel milk caused the reverse. Both types of camel milk revealed significant decrease in the blood TAG levels and were statistically validated. Thus, the present study recommends the choice of camel milk consumption especially in diabetic patients as well, as an immunity booster in the wake of the present environmental health issues.